УРОВНИ ТЕРРИТОРИАЛЬНОЙ ОБОРОНЫ УКРАИНЫ - Калгушкин, Юрий Леонидович (SUPREMANCE OF LAW, 2018)
The article presents a theoretical generalization and a new solution of the scientific problem, which consists in the definition of new approaches to the problem of determining the levels of territorial defense of Ukraine. The author defines the notion of level of territorial defense, which is proposed to understand the form of “horizontal” distribution of powers of territorial defense entities with a view to its effective organization, provision and implementation. Taking into account the lack of normative consolidation of this problem, we are given our own vision, according to which the following levels of territorial defense should be distinguished: 1) national; 2) local; 3) special. Each level is characterized by a number ofpeculiarities, and also has the corresponding normative expression. The thesis is based on the fact that the formation of this category is carried out at the national level of territorial defense, as well as a general definition of powers and other aspects of interaction between its subjects. It is noted that at the local level, territorial defense is implemented and provided by local executive authorities and self-government bodies. The latter within the limits of the competence provided by the legislation issue normative acts on issues related to the development and organization of territorial defense. It is noted that the special level of territorial defense is the level of activity of separate law enforcement bodies and military formations, which are trampled by subjects of territorial defense. Within this framework, the work of the abovementioned departments is being improved to ensure the effective implementation of the tasks of territorial defense in the future, as reflected in the departmental regulatory framework of each individual body.